RANCANG BANGUN APLIKASI PEMANTAU RUANGAN MELALUI KAMERA IP MENGGUNAKAN PLATFORM ANDROID (STUDI KASUS : LABORATORIUM TEKNIK INFORMATIKA UNIVERSITAS TANJUNGPURA) - Ashardi, Dedy (Jurusan Informatika Universitas Tanjungpura, 2013)
Nowadays, information technology andmobility development with the need of moreconvenience and faster data access especially inmonitoring or surveillance of a building have becomea matter of urgency. One of the example is mobiledevice or mobile phone that has the technology toaccess the image using IP-based cameras that used ascamera monitors. The live streaming monitoringsystem in general use devices such as cameras andtelevisions or computers as the device hardware. Withthis monitoring system, users will allow to takeadvantage of this system that restricted only to thesame place with a television or computer monitorused. Therefore, it can be developed a dedicatedmobile application for devices with Android platformthat provide the ability to access the IP cameramonitoring via live streaming and historicalmonitoring of IP cameras that stored into the storage,so it can be optimized by the user when needed. Thetest results showed that the application can monitorlive streaming building with MJPEG format onAndroid mobile devices.